2020
DOI: 10.3390/molecules25163667
|View full text |Cite
|
Sign up to set email alerts
|

Glucosamine Enhancement of BDNF Expression and Animal Cognitive Function

Abstract: Brain-derived neurotrophic factor (BDNF) is an important factor for memory consolidation and cognitive function. Protein kinase A (PKA) signaling interacts significantly with BDNF-provoked downstream signaling. Glucosamine (GLN), a common dietary supplement, has been demonstrated to perform a variety of beneficial physiological functions. In the current study, an in vivo model of 7-week-old C57BL/6 mice receiving daily intraperitoneal injection of GLN (0, 3, 10 and 30 mg/animal) was subjected to the novel obje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Neurotrophic factors play a crucial role in neurogenesis ( Agrimi et al, 2019 ). It has been found that BDNF is an important neurotrophic factor and its signaling inhibits autophagy in an adult brain by transcriptionally downregulating key ( Patterson, 2015 ; Chou et al, 2020 ) components of the autophagy machinery and that genetic ablation of BDNF in the nervous system leads to uncontrolled increases in autophagy in the adult brain and is associated with severe synaptic defect ( Nikoletopoulou et al, 2017 ). Decreased levels of BDNF in the hippocampus can aggravate cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Neurotrophic factors play a crucial role in neurogenesis ( Agrimi et al, 2019 ). It has been found that BDNF is an important neurotrophic factor and its signaling inhibits autophagy in an adult brain by transcriptionally downregulating key ( Patterson, 2015 ; Chou et al, 2020 ) components of the autophagy machinery and that genetic ablation of BDNF in the nervous system leads to uncontrolled increases in autophagy in the adult brain and is associated with severe synaptic defect ( Nikoletopoulou et al, 2017 ). Decreased levels of BDNF in the hippocampus can aggravate cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Upon its translocation to the nucleus, activated CREB endorses the transcription and expression of its target genes BDNF and its cognate receptor TrKB ( Nair and Vaidya, 2006 ; Chou et al, 2020 ). This verity has been mirrored herein, since following the activated cAMP/p-CREB axis, Lira succeeded to oppose the effect of 3-NP and augmented the striatal contents of BDNF and the protein expression of its receptor TrKB.…”
Section: Discussionmentioning
confidence: 99%
“…AD is known for the deposition of amyloid β aggregates in the central nervous system and retina, and AMD is known for amyloid β deposits in drusens and the RPE from studies with donor human eyes [ 26 , 31 ]. A cross-sectional study reported that GlcN is associated with beneficial cognitive function [ 32 ] and in in vivo studies, GlcN can increase the level of brain-derived neurotrophic factor, which is involved in memory consolidation and cognitive function [ 33 ]. With these numerous similarities, one can hypothesize that GlcN may be beneficial for patients with AMD as well; however, further research is needed.…”
Section: Discussionmentioning
confidence: 99%